Analisis Rule of Reason terhadap Penyalahgunaan Posisi Dominan (Studi Komparatif: Indonesia, Uni Eropa, dan Amerika Serikat) - , VEGITYA RAMADHANI-PUTRI, SH, S.ANT, Prof. M. Hawin, S.H., LL.M., Ph. D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Law enforcement against abuse of dominance in Antimonopoli Act of Indonesia needs Rule of Reason as analytical method. The inquiries determines the existence of dominance and the existence of abuse of dominance. Indication of the existences, such as: measurement of definition of relevant market, market power, market consentration, market share, and entry barriers. Accordingly, the indicators of abuse of dominance are dependentcy among competitors, harms or damages on competitors, effects on consumers, and disinsentives for others counterparts, qualitatively as well as quantitatively. Abuse of dominance that regulated at Competition Law in European Communities based on Article 82 Rome Treaty. According Article 82 Rome Treaty, any abuse by one or more undertakings of a dominant position within the common market or in a substantial part of it shall be prohibited as incompatible with the common market insofar as it may affect trade between EC Member States. Such abuse may, in particular, consist in: (a) directly or indirectly imposing unfair purchase or selling prices or other unfair trading conditions